Applicability of linear elastic fracture mechanics to compressive damage in carbon fiber reinforced epoxy matrix composites. Issue 26 (26th October 2022) - Carpenter, K.; Lei, Y.; Asadi, A.; Parmigiani, J.; Tabei, A.
Abstract: The failure of carbon fiber reinforced epoxy matrix composites has been attributed to different mechanisms involving tensile, compressive and shear failure of the fibers or the matrix. This research serves to understand whether linear elastic fracture mechanics can explain the matrix behavior under compressive loading. Experiments and finite element analysis (FEA) are used to confirm that the matrix under compressive loads follows the relationships established by linear elastic fracture mechanics. The failure load is related to the corresponding notch length, and the observed relationship is compared to the relationship defined by linear elastic fracture mechanics.